Legal action of a competitor of a beneficiary of Slovenian state aid before ordinary courts in Slovenia - Jorg Sladič (LeXonomica, 2021)
Illegal state aids are distorting the competition by merits. The beneficiaries of state aids have a competitive advantage compared to their competitors. The article examines remedies that a competitor can lodge before ordinary courts in Slovenia. The competitor can lodge an action for declaration as well as an action for a compelling order. Each action has its own ambit and plays its own role in the field of state aid. Therefore, an action for declaration shall not be deemed merely as a subsidiary of an action for a compelling court order. EU law contains a right to have a validity of contracts of private law by which a state aid has been granted. In Slovenian civil procedure this means that the competitor can apply for a declaration of voidness of a contract infringing rules on state aids. However, it a state aid has been granted by a general and abstract measure or an individual administrative act, the competitor cannot apply for a declaration of invalidity of such a measure or administrative act before ordinary courts. A competitor can however apply for a declaration of existence of a state aid in such a case.Tožba konkurenta prejemnika slovenske državne pomoči pred rednim sodiščem v Sloveniji. Nezakonite državne pomoči izkrivljajo konkurenco na trgu. Prejemniki takšne državne pomoči imajo konkurenčno prednost v razmerju do svojih konkurentov. Prispevek analizira možnosti, ki jih ima konkurent, da doseže pravno varstvo pred rednimi sodišči. Konkurent lahko vloži pred rednimi sodišči tako dajatveno kot ugotovitveno tožbo, saj imata na področju državnih pomoči obe različno vlogo, tako da ni subsidiarnosti ugotovitvene tožbe v razmerju do dajatvene. Pravo EU konkurentu celo daje pravico do vložitve ugotovitvene tožbe za preskus veljavnosti (zasebnopravnih) aktov, s katerimi je podeljena pomoč. To pa v slovenski obliki civilnega postopka pomeni, da lahko konkurent pred civilnimi sodišči zahteva ugotovitev ničnosti pogodbe, s katero so kršena pravila o državni pomoči. Če pa je pomoč podeljena s predpisom ali z upravno odločbo, pa konkurent ne more zahtevati ugotovitve neveljavnosti predpisa ali odločbe pred rednimi sodišči, lahko pa toži na ugotovitev, da določen predpis ali pa odločba pomenita nezakonito državno pomoč.